Upaya Perlindungan Hukum Terhadap Perusakan Lingkungan Yang Disebabkan Oleh Galian C Di Provinsi Bali - I Ketut Pongres; I Made Suardika Jaya (PARIKSA: Jurnal Hukum Agama Hindu, 2021)
Exploitation of class C minerals is the extraction of class C minerals from natural resources in and or on the surface of the earth for use. As a result of mining of group C minerals, it can cause erosion of the soil's topsoil, which is the top layer of the soil surface which can contain organic material called nutrients and is dark in colour due to the accumulation of organic matter in this layer which is called processing which is the main area for plants. So that, this damage can have an impact on the surrounding environment such as land, gardens, agriculture and the like as well, thus this can affect the condition of the tourism environment in Bali. Therefore, legal protection is needed to protect the former excavated area C from damage. Next, two problem formulations can be formulated, the first problem formulation is how the basis for the authority of the Bali Provincial Civil Service Police Unit in dealing with environmental destruction due to former excavation C. The second problem formulation is how the implementation of the authority of the Civil Service Police Unit of Bali Province in dealing with environmental destruction due to the former excavation C. The purpose of this paper is to determine the extent to which legal protection efforts against environmental destruction resulting from excavation C have been carried out by the Bali Provincial Civil Service Police Unit. The methodology used in this paper is a qualitative methodology. It can be concluded that the basis for the authority of the Civil Service Police Unit in carrying out law enforcement efforts against environmental destruction in former excavation C is Law number 23 of 2014 concerning regional governance and regional regulation of Bali Province number 4 of 2014 concerning management of non-metal mineral and rock mining, in which in practice the Bali Provincial Civil Service Police Unit coordinates with the Regency / City Civil Service Police Unit whose territory has the potential for excavation C.